The Role of Entrepreneurship in Facing Global Economic Challenges - Santoso, Raditya; Budiono, Iskandar; Joshua, Cristiano (JMEB Jurnal Manajemen Ekonomi & Bisnis, 2024)
This research confirms that entrepreneurship plays an important role in overcoming global economic challenges and driving economic growth in Indonesia. Findings from in-depth interviews, quantitative data analysis, case studies of entrepreneurship programs, and literature reviews show that entrepreneurship not only adapts to market changes and geopolitical uncertainty, but is also a major motor of sustainable economic growth. Innovative entrepreneurs have the ability to turn challenges into opportunities, with important support from the government and related sectors. Although data shows a positive relationship between entrepreneurship and reduced unemployment, efforts are still needed to increase the number of entrepreneurs and ensure the sustainability of entrepreneurship programs. Evidence-based policy recommendations, such as increasing access to funding and providing specific training, as well as synergy between stakeholders, are key to strengthening the role of entrepreneurship in overcoming global economic challenges and advancing inclusive economic growth in Indonesia.